The Soil-Anchors System Theories and Improvement: A Review Study - Ali R. Daibil; A’amal A. H. Al-Saidi (Journal of Engineering, 2025)
In this paper, researchers have employed various methods and experimental ways to investigate the behavior of the soil-anchors system under the influence of varying load conditions. Also to focus on studying this system with improving the soil under loading with the anchor as a system. Therefore, the effect of soil geogrid improves the vertical anchor plates performance, and the test results show that the size, location, height, position, water content of the improved mass, and the variation of pullout load angle (0,25.45.60,90) degrees affect the resistance of the vertical anchor plate. But the improving the soil-anchors system with compaction the soil surrounding the anchor, adding the cement to soil, and improving with lime, that showed when the ratio of the improvement soil to the anchor-plate diameter be (D/d=1, D/d=1.5) with adding cement to soil and lime in other test in a percent less than 3%, the compaction test was the best in the evaluate the pull out of the soil-anchor system. If the percentage of the added cement to the soil is 6%, this will be more efficient in the strengthening process than compaction and lime. clayey layers above anchor plate, when loading the anchor plate by pull out in the physical model, the vertical displacement is increasing when increase the water content of the clay layer, also if the clayey layer in the solid state is above the sandy layer gives more displacement than the sandy layer above the clayey layer.